2014
DOI: 10.2196/jmir.3084
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Sustained Use of a Free Mobile App for Dietary Self-Monitoring With Photography and Peer Feedback: Retrospective Cohort Study

Abstract: BackgroundHealthy eating interventions that use behavior change techniques such as self-monitoring and feedback have been associated with stronger effects. Mobile apps can make dietary self-monitoring easy with photography and potentially reach huge populations.ObjectiveThe aim of the study was to assess the factors related to sustained use of a free mobile app (“The Eatery”) that promotes healthy eating through photographic dietary self-monitoring and peer feedback.MethodsA retrospective analysis was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
105
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(117 citation statements)
references
References 35 publications
11
105
0
1
Order By: Relevance
“…Twenty-four studies were aimed at general nutrition improvement, 11 weight loss, 5 grocery-shopping support, 4 food-access support, and 3 parenting support. Five of the applications described were commercial applications (LoseIt!, FatSecret's Calorie Counter, and The Eatery) (38,40,41,43,78), whereas the remainder were developed by research teams (hereafter "made to order"). Twenty-three studies were conducted in the United States, 8 in Australia, 6 in the United Kingdom, 2 in Norway, and 1 each in Austria, Canada, Finland, Korea, Malaysia, the Netherlands, New Zealand, and Portugal.…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-four studies were aimed at general nutrition improvement, 11 weight loss, 5 grocery-shopping support, 4 food-access support, and 3 parenting support. Five of the applications described were commercial applications (LoseIt!, FatSecret's Calorie Counter, and The Eatery) (38,40,41,43,78), whereas the remainder were developed by research teams (hereafter "made to order"). Twenty-three studies were conducted in the United States, 8 in Australia, 6 in the United Kingdom, 2 in Norway, and 1 each in Austria, Canada, Finland, Korea, Malaysia, the Netherlands, New Zealand, and Portugal.…”
Section: Overviewmentioning
confidence: 99%
“…Adults and overweight populations generally valued quiz-style games if they were quick to play and included incentives such as real rewards (70,74,85). Competition, team participation, and social interaction motivated engagement with applications across all population groups (48,50,77,78,80,90,99), but negative scoring of points was not well understood by low-SES populations (77). Young adults in particular emphasized that social networking and sharing must be voluntary and not automatic (65,93,98,99).…”
Section: Evaluation Of Featuresmentioning
confidence: 99%
“…In a more recent study, people tried out a free mobile app that promotes healthy eating through photographic dietary self-monitoring and peer feedback. 54 In that study, "actives" (defined as users who had taken at least 10 pictures and used the app for at least 1 week) were more likely to have at least one comment or "like" from other users for the picture they uploaded than semiactives (users with 2 to 9 pictures) and nonactives (dropouts with one picture). 54 …”
Section: Use Mobile Device/applications With Instant Feedbackmentioning
confidence: 95%
“…The study reported low adherence and only a small percentage of individuals saw a positive trend in their average healthiness ratings. 54 Another study reported that photography approximated but underreported the intakes achieved with the most rigorous (weighed) food records. 45 It is still difficult to estimate food ingredients and portion sizes from a photograph, but new technology based on image processing or crowd sourcing might solve the problem.…”
Section: Mobile Devicesmentioning
confidence: 99%
“…The widespread use of mobile phone technology means that this is an ideal platform for the confidential monitoring and modulation of patient behaviour [9] [10]. In addition, serious games and social media are emerging genres which combine behavioural change interventions with entertainment to provide an engaging medium which can produce beneficial health behaviour changes [11].…”
Section: A Mobile Applications To For Diet Control and Exercisetmentioning
confidence: 99%